Criminal Acts Against Spanish Tourist Couples: A Critical Discourse Analysis Teun A. Van Dijk - Sari, Arini Vika; Pariyasto, Sofyan; Monteres, Arlestito (Journal of Advance in Language, Literature, and Education, 2025)
Criminal acts such as assault or rape are things that cannot be tolerated. This research uses qualitative data with descriptive methods. Data collection techniques were carried out through documentation, attention, and notes. As for the analysis method, the approach is based on the Critical Discourse Analysis model of Teun A. Van Dijk. Based on the discourse analysis of the news discourse of Spanish celebrities raped by 7 people in India, 4 suspects were arrested published by CNN Indonesia media, it can be concluded that the news preparation structure has a conceptual framework following Teun A. Van Dijk's theory which includes macro structure, superstructure and micro structure. Microstructure is a dimension of AWK that has the most detailed discussion. The microstructure consists of semantics, which consists of 6 data, syntax has 8 data, and rhetoric consists of 2 data. The level of a person's understanding in conducting discourse analysis on a news discourse can influence the perception to respond to the contents of the news.